Post-mortem and histological lesions in the European minks (Mustela lutreola) induced by spontaneous infection with coronavirus SARS-CoV-2 - I. A. Subbotina; I. N. Gromov (Ветеринария сегодня)
The paper contains data on registration of the SARS-CoV-2 virus in the European mink population. Profound and detailed studies of the virus circulation in the European mink population and the clinical manifestations of the disease, comprehensive approaches to the disease diagnosis, including epidemiological studies, clinical and post-mortem examinations, molecular genetic laboratory diagnostics (polymerase chain reaction and full-genome sequencing) contributed to better understanding of the disease features. The paper presents the data on post-mortem and histological lesions in the European minks infected with the new coronavirus SARS-CoV-2 obtained during the research. All the animals from which the pathological material was collected were infected with SARS-CoV-2, and the diagnosis was made using polymerase chain reaction (RT-PCR). The obtained and presented in the paper data reveal the features and dynamics of pathological processes in the body of infected animals (European mink), demonstrate the characteristics of the lesions in organs and tissues in case of acute and chronic disease, explain the clinical and post-mortem disease pattern and indicate the causes of animal deaths. All this together will allow veterinary specialists not only to quickly and timely diagnose the disease in the population of fur animals (European mink), but also to take necessary therapeutic and preventive measures in a timely manner, to select the most effective means for symptomatic and pathogenetic therapy as well as the most rational and effective substances and disinfection procedures.